A PESQUISA EM GESTÃO DA SUSTENTABILIDADE AMBIENTAL: EVOLUÇÃO INTELECTUAL E AGENDA FUTURA A PARTIR DE UM ESTUDO BIBLIOMÉTRICO DE CITAÇÃO E COCITAÇÃO - Marco André de Carvalho Assan (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2018)
The aim of this article is to understand the intellectual structure that connects theories and authors researching environmental sustainability management in relation to the challenges facing organizations. To propose a research agenda on the theme, a bibliometric study was conducted of the articles published in international journals indexed in the Web of Science – ISI Web of Knowledge database. Four renowned periodicals for the years available in this database were considered: Business Strategy and the Environment (IF=2,877), Corporate Social Responsibility and Environmental Management (IF=2,804), Ecological Economics (IF=4,062) and the Journal of Environmental Economics and Management (IF=3,398). A bibliometric analysis of the selected articles in the field of sustainability management identified the most referenced works, the most relevant publications and periodicals in the sample. The co-citation analysis showed the conceptual relationships between the works on which the theme was founded, and identified the trends in studies in the field. The results showed three major fields of study: 1) “Importance of and Challenges for Environmental Sustainability” (linked to three other subfields of study: “Warnings, Urgency and Evaluation of Sustainability” (F2), “Costs and Risks of Non Sustainability” (F4) and “Value of Environmental Goods and Services” (F5); 2) “Economic Growth and the Environment” (F1); and 3) “Sustainability and Competitive Advantage” (F3). This article aids a better understanding of the theme of environmental sustainability and provides orientation for future studies.